The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1007/s00432-020-03126-9
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 expression and survival in p16-negative and -positive squamous cell carcinomas of the vulva

Abstract: Aim Programmed death-ligand 1 (PD-L1) has become a widely used predictive biomarker for therapy with checkpoint inhibitors in a variety of cancers. Here, we studied the expression of PD-L1 in squamous cell carcinomas of the vulva (SCCV) with regard to HPV status via its surrogate marker p16. Additionally, the status of PD-L1 and p16 were analyzed for prognostic information and potential correlation to tumor-infiltrating lymphocytes (TILs). Methods PD-L1 was analyzed in 128 cases of SCCV using the tumor proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Our research group has already investigated a proven positive effect of p16 on the prognostic outcome of patients with VSCC. p16 positive VSCC revealed a longer overall and progression free survival [ 106 ]. It also appears in some other studies that HPV-associated VSCC have a better clinical outcome as Sand et al [ 107 ] reported in a recent review.…”
Section: Discussionmentioning
confidence: 99%
“…Our research group has already investigated a proven positive effect of p16 on the prognostic outcome of patients with VSCC. p16 positive VSCC revealed a longer overall and progression free survival [ 106 ]. It also appears in some other studies that HPV-associated VSCC have a better clinical outcome as Sand et al [ 107 ] reported in a recent review.…”
Section: Discussionmentioning
confidence: 99%
“…Sections from entire tumor blocks were used to account for the intratumoral heterogeneity and variability of the PD-L1 expression. They were processed as described previously [37]. Briefly, sections were cut from paraffin blocks and mounted on SuperFrost Plus ® microscopy slides (Menzel Gläser, Braunschweig, Germany).…”
Section: Analysis and Scoring Of Pd-l1 And P16 Expressionmentioning
confidence: 99%
“…Only the membranous reactivity of carcinoma cells was considered and quantified relating to the amount of vital carcinoma cells. For further analysis and stratification, we applied scores referred to as TPS 0 (TPS < 1%), TPS 1 (1% ≤ TPS < 5%), TPS 2 (5% ≤ TPS < 10%), TPS 3 (10% ≤ TPS < 25%), TPS 4 (25% ≤ TPS < 50%), and TPS 5 (TPS ≥ 50%) [37]. Positivity for p16 was defined by strong cytoplasmic and nuclear staining throughout the whole tumor on a slide ("block" staining).…”
Section: Analysis and Scoring Of Pd-l1 And P16 Expressionmentioning
confidence: 99%
“…Furthermore, there might be different definitions of p16 positivity in immunohistochemistry [ 43 ]. Exclusively strong cytoplasmic and nuclear “block like” staining throughout the whole tumor on slide should be considered as p16-positive [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…EP4 promotes its tumorigenic effect through several processes in the microtumor environment. Inter alia, previous studies identified PDL-1 expression as being a negative prognosticator in squamous cell carcinoma of the vulva and showed that the number of tumor infiltrating lymphocytes was associated with PD-L1 expression [ 44 ]. According to Wang et al, stimulation of PGE2/EP4 signaling pathways resulted in an increased expression of PD-1 in infiltrating CD8+ T-cells in patients with lung cancer [ 45 ].…”
Section: Discussionmentioning
confidence: 99%